Venous thromboembolism risk score during hospitalization in pregnancy: results of 10694 prospective evaluations in a clinical trial (Clinics, 2023)
Objectives: Hospitalization during pregnancy and childbirth increases the risk of Venous Thromboembolism Risk (VTE). This study applied a VTE risk score to all hospitalized pregnant women to ascertain its effectiveness in preventing maternal death from VTE until 3 months after discharge.Methods: In this interventional study, patients were classified as low- or high-risk according to the VTE risk score (Clinics Hospital risk score). High-risk patients (score ≥ 3) were scheduled for pharmacological Thromboprophylaxis (TPX). Interaction analysis of the main risk factors was performed using Odds Ratio (OR) and Poisson regression with robust variance.Results: The data of 10694 cases (7212 patients) were analyzed; 1626 (15.2%, 1000 patients) and 9068 (84.8%, 6212 patients) cases were classified as high-risk (score ≥ 3) and low-risk (score < 3), respectively. The main risk factors (Odds Ratio, 95% Confidence Interval) for VTE were age ≥ 35 and < 40 years (1.6, 1.4–1.8), parity ≥ 3 (3.5, 3.0–4.0), age ≥ 40 years (4.8, 4.1–5.6), multiple pregnancies (2.1, 1.7–2.5), BMI ≥ 40 kg/m2 (5.1, 4.3–6.0), severe infection (4.1, 3.3–5.1), and cancer (12.3, 8.8–17.2). There were 10 cases of VTE: 7/1636 (0.4%) and 3/9068 (0.03%) in the high- and low-risk groups, respectively. No patient died of VTE. The intervention reduced the VTE risk by 87%; the number needed to treat was 3.Conclusions: This VTE risk score was effective in preventing maternal deaths from VTE, with a low indication for TPX. Maternal age, multiparity, obesity, severe infections, multiple pregnancies, and cancer were the main risk factors for VTE.